2013
DOI: 10.1016/j.biomaterials.2013.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced wound healing by topical administration of mesenchymal stem cells transfected with stromal cell-derived factor-1

Abstract: The objective of this study was to investigate the ability of mesenchymal stem cells (MSC) genetically engineered with stromal cell-derived factor-1 (SDF-1) to heal skin wounds. When transfected with SDF-1 plasmid DNA, MSC which were isolated from the bone marrow of rats, secreted SDF-1 for 7 days. In vitro cell migration assay revealed that the SDF-1-engineered MSC (SDF-MSC) enhanced the migration of MSC and dermal fibroblasts to a significantly greater extent than MSC. The SDF-MSC secreted vascular endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 46 publications
2
75
0
Order By: Relevance
“…Various risk factors, however, such as diabetes, hypoxia, ischemia, and infection, lead to dysfunction of various types of cells and to production of soluble mediators, resulting in wound underhealing or overhealing. Recently, several studies showed that local or systemic administration of stem or progenitor cells, such as mesenchymal stem cells (MSCs) and EPCs, enhances wound repair and angiogenesis [10, 21]. In particular, these studies revealed that the use of genetically engineered cell populations could increase the therapeutic efficacy, because the harsh pathological environment, including hypoxia, drastically affects the survival rate of the unmodified transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various risk factors, however, such as diabetes, hypoxia, ischemia, and infection, lead to dysfunction of various types of cells and to production of soluble mediators, resulting in wound underhealing or overhealing. Recently, several studies showed that local or systemic administration of stem or progenitor cells, such as mesenchymal stem cells (MSCs) and EPCs, enhances wound repair and angiogenesis [10, 21]. In particular, these studies revealed that the use of genetically engineered cell populations could increase the therapeutic efficacy, because the harsh pathological environment, including hypoxia, drastically affects the survival rate of the unmodified transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cell pellets were redispersed in M199 (GIBCO) supplemented with 10% FBS and 1% endothelial cell growth supplement/ heparin kit (ECGS/H, Promocell). Primary dermal fibroblasts were isolated and subcultured using a method described previously [46]. Briefly, the skin specimens were cut into small pieces with surgical scissors, placed in a 10 cm tissue culture dish and cultured in DMEM supplemented with 10 vol% FCS and 1 wt.% P/S at 37 C in a humidified atmosphere composed of 5% CO 2 .…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…[1] In particular, chronic diabetic foot ulcers (DFUs) are responsible for more than 73,000 nontraumatic lower limb amputations and impose a substantial cost burden on public and private payers, with costs ranging from $9–$13 billion in addition to the costs associated with diabetes itself. [2] Despite the use of autografts, tissue engineered products, and wound dressings of various types, [3] successful treatment of chronic DFUs remains elusive and currently there is no widely used effective therapy. [4] Therefore, new cost-effective, safe, and efficacious strategies are warranted to improve the care for hard-to-heal DFUs.…”
Section: Introductionmentioning
confidence: 99%